Extracellular xenogeneic hemoglobin suppresses the capacity for C2C12 myoblast myogenic differentiation - Stančić, Ana Z.; Drvenica, Ivana T.; Bugarski, Branko M.; Ilić, Vesna Lj.; Bugarski, Diana S. (Archives of Biological Sciences, 2020)
Paper description: As a part of their microenvironment, extracellular hemoglobin has the potential to modify functional characteristics of satellite cells that act as myogenesis initiators. The effect of extracellular xenogeneic hemoglobin (porcine and bovine) was investigated on myoblast proliferation, migration and differentiation capacity, using C2C12 cells as a model. Extracellular hemoglobin modifies C2C12 cell proliferation and migration in a dose- and time-dependent manner and suppresses myogenic differentiation. These findings are important for treating muscle injuries in patients with hemoglobinemia-related diseases and conditions, especially when using satellite cells for cell therapy as the presence of extracellular hemoglobin can influence its outcome. Abstract: Functional characteristics of satellite cells (SCs) that act as myogenesis initiators and have emerged as a promising target for cell therapy, are dependent on their microenvironment. The aim of this study was to investigate the effect of cell-free hemoglobin, as a part of the microenvironment of SCs, on their functional characteristics. The C2C12 cell line served as the experimental model of the SC experimental model; hemoglobin isolated from porcine (PHb) and bovine (BHb) slaughterhouse blood served as the extracellular hemoglobin. The proliferation rate of C2C12 cells was assessed by the MTT test, migration capacity by the scratch assay, and myogenic differentiation capacity by histochemical staining and RT-PCR analysis of the expression of genes specific for myogenic lineage. The effect of hemoglobin on the proliferation and migration of C2C12 cells was dependent on its concentration and the animal species it was isolated from, but the effect of BHb was more prominent. Both PHb and BHb decreased the expression levels of myogenin and muscle specific creatine kinase at a 10 µM concentration. While PHb had no effect on the morphometric parameters of C2C12 myotubes, BHb modified the area and length of C2C12 myotubes cultivated in DMEM/2% horse serum and DMEM/10% fetal calf serum. While PHb and BHb had no effect on heme oxygenase 1 (Hmox1) expression, they stimulated the expression of hypoxia-inducible factor 1-alpha (Hif1α) at a concentration of 10 µM. The mainly inhibitory effect of cell-free hemoglobin on myogenic differentiation suggests that it could be a relevant factor in the outcome of cell therapy of muscle injury. https://doi.org/10.2298/ABS200625032S Received: June 25, 2020; Revised: August 8, 2020; Accepted: August 10, 2020; Published online: August 25, 2020 How to cite this article: Stančić AZ, Drvenica IT, Bugarski BM, Ilić VL, Bugarski DS. Extracellular xenogeneic hemoglobin suppresses the capacity for C2C12 myoblast myogenic differentiation. Arch Biol Sci. 2020;72(3):379-91.